Analysis of the Bumdes Institutions Existence on Community Income Levels (Case Study in Waeapo District, Buru Regency) - Nur Haida; Wardis Girsang; Natelda Rosaldiah Timisela; Sri Anggasari Makatita (Agribusiness Department, Agriculture Faculty, Tanjungpura University, 2022)
BUMDES is a program designed by the government with an approach to utilizing the potential of natural resources in the village through village innovation activities. Waeapo District is a district that develops the concept of rural development based on village potential through BUMDES institutions, most of the superior potential in Waeapo District is agriculture. This research aims to describe the business type of BUMDES and to identify factors that influence the development and sustainability of the BUMDES institution as a strategic instrument to realize village economic independence. The research sample used in this study is Amanah Umat BUMDES, Karya Dewata Mandiri BUMDES, and 32 Respondents. The data ware analyzed descriptively with a SWOT matrix to analyze development and sustainability factors. Results of the study show that Amanah Umat BUMDES has types of savings and loan businesses, Saprodi, BNI agent, fattening cattle, public saving, and saving students. BUMDES by Dewata Karya Mandiri has types of businesses selling pulses, borrowing fertilizers, rice milling, renting cars, and selling motorcycle equipment. Factors that influence BUMDES institution are internal factors and external factors.